The influence of client incivility and coping strategies on audit professionals' judgments - Bauer, Tim D.; Hillison, Sean M.; Mokhtar, Ala (Contemporary Accounting Research, 2025)
Prior research demonstrates that audit professionals encounter client incivility. We extend this research by examining whether client incivility negatively impacts auditors' judgments and whether any adverse effects are reduced when auditors use coping strategies. We first collect descriptive survey evidence revealing that client incivility toward auditors is more widespread than currently documented. Next, using an experiment, we predict and find that auditors who experience client incivility (vs. those who do not) are less likely to challenge aggressive reporting if they are not prompted to cope. We also find that active coping reduces the adverse impact of client incivility, whereas findings for passive coping are inconclusive. Audit standards and users of financial statements expect auditors to fulfill their duty of maintaining a high level of professional skepticism irrespective of external circumstances. Our findings highlight the challenges auditors face in meeting these expectations when facing uncivil clients, thus posing a threat to audit quality.